2022
DOI: 10.3390/ijms23137151
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of CXCL1 in the Physiological State and in Noncancer Diseases of the Oral Cavity and Abdominal Organs

Abstract: CXCL1 is a CXC chemokine, CXCR2 ligand and chemotactic factor for neutrophils. In this paper, we present a review of the role of the chemokine CXCL1 in physiology and in selected major non-cancer diseases of the oral cavity and abdominal organs (gingiva, salivary glands, stomach, liver, pancreas, intestines, and kidneys). We focus on the importance of CXCL1 on implantation and placentation as well as on human pluripotent stem cells. We also show the significance of CXCL1 in selected diseases of the abdominal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 215 publications
2
15
1
Order By: Relevance
“…Previous studies have shown that CXCL1 is a proin ammatory cytokine in various viral and nonviral hepatitis types and is positively correlated with chronic hepatocyte injury and the progression of cirrhosis (14,19). The pro-tumor in ammatory effects of CXCL1 in the liver have been systematically…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CXCL1 is a proin ammatory cytokine in various viral and nonviral hepatitis types and is positively correlated with chronic hepatocyte injury and the progression of cirrhosis (14,19). The pro-tumor in ammatory effects of CXCL1 in the liver have been systematically…”
Section: Discussionmentioning
confidence: 99%
“…It also regulates liver fibrogenesis by activating hepatic stellate cells. CXCL1 exerts its function in liver disease mainly by regulating neutrophils, Kupffer cells and myeloid-derived suppressor cells (MDSCs), and its specific receptor CXCR2 is highly enriched [ 18 , 19 ]. In this research, based on evidence from HCC clinical samples, CXCL1 expression is positively correlated with the infiltration of macrophages and the ratio of CD206-positive macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CXCL1, IL-12p40 and IL-1RA were increased after both treatments. CXCL1 and IL-12p40 are immunomodulatory molecules which have been related to T2D and other inflammatory conditions [33,34], acting as chemoattractant for several immune cells, especially neutrophils and macrophages, respectively. In addition, IL-12p40 provides a negative feedback loop by competitively binding the pro-inflammatory IL-12 receptor [34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, IL-1RA is a natural anti-inflammatory factor and mediator in glucose homeostasis disturbances that blocks IL-1α and IL-1β signalling[35]. While the increase in CXCL1 after olive oil treatments is puzzling given the current lack of studies on the role of this small peptide in obesity and diabetes pathogenesis[33], those of IL-12p40 and IL-1RA fits well with an anti-inflammatory effect mediated by blockage of pro-inflammatory signalling through IL-12 and IL-1 receptors, respectively[34,35]. Interestingly, IL-12p40 has also been found to suppress IFN-γ secretion [36], a cytokine produced during chronic inflammation and also related to the events initiating obesity-induced adipose tissue inflammation and insulin resistance[37].…”
Section: Discussionmentioning
confidence: 99%